Mathematical Modeling to Analyse the Impact of Vaccine Efficacy, Media and the Treatment Rate on the Transmission Dynamics of SARS CoV-2 Virus: a case study of the most affected East Asian Countries - Negi, Sunil Singh; Sharma, Nitin; Rana, Pankaj Singh (Journal of Applied Nonlinear Dynamics, 2026)
A deterministic compartment model for the transmission dynamics of coronavirus is formulated in this article. The impact of vaccine efficacy, media effect, and the cure rate of hospitalized individuals is investigated. The threshold quantity basic reproduction number (R_0) characterizes the SARS-CoV-2 transmission. It has been observed that the disease-free equilibrium is globally asymptotically stable for R_01, and the endemic equilibrium point is globally asymptotically stable for R_0>1. The global stability of both the equilibrium points is demonstrated via the Lyapunov function. The developed model has been fitted to the reported cumulative cases for the four most affected East Asian countries namely China, Japan, South Korea, and Taiwan to estimate the parameters. The numerical results indicate that increasing vaccine efficacy u_1, treatment, and media effect can aid in controlling the spread of disease, reducing disease-induced mortality, and improving recovery.